2020
DOI: 10.1002/brb3.1718
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia‐inducible factor 1α, glucose transporter 1, and hexokinase 2 in primary central nervous system lymphoma and the correlation with the biological behaviors

Abstract: Background It has been indicated that abnormal glucose metabolism mediated by hypoxia‐inducible factor 1α (HIF‐1α) played an essential role in the development of solid tumor. However, there were rare studies about the role of them in primary central nervous system lymphoma (PCNSL). Objective To investigate the protein levels of HIF‐1α, glucose transporter 1 (GLUT1), and hexokinase 2 (HK2) in PCNSL and whether their levels are associated with prognostic factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Persistent hypoxia can additionally enhance local and systemic malignant progression and may also extend increase invasiveness through the clonal selection and genomic and proteomic changes (Dachs and Chaplin, 1998). HIF-1α is a major regulator of glycolysis (Shen et al, 2020). Under hypoxia, HIF-1α plays an important role in the transcription of genes involved in angiogenesis, tumor growth, invasion, metastasis, and glucose metabolism (Soni and Padwad, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hypoxia can additionally enhance local and systemic malignant progression and may also extend increase invasiveness through the clonal selection and genomic and proteomic changes (Dachs and Chaplin, 1998). HIF-1α is a major regulator of glycolysis (Shen et al, 2020). Under hypoxia, HIF-1α plays an important role in the transcription of genes involved in angiogenesis, tumor growth, invasion, metastasis, and glucose metabolism (Soni and Padwad, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is an important transcription factor that regulates glucose uptake and glycolysis at the transcriptional level (Huang et al, 2012 ; Harris et al, 2014 ; Masoud and Li, 2015 ). Several studies have shown that HIF-1α upregulates glucose transporters (GLUT1, GLUT3, GLUT4; Toberer et al, 2020 ), glycolysis enzyme (HK2; Cao et al, 2020 ; Shen et al, 2020 ), pro-angiogenic factors (HO-1, VEGF; Choi et al, 2006 ). Whereas, downregulation of HIF-1α suppressed the target genes and protein expressions, such as GLUT1, GLUT3, and HK2 (Liu et al, 2008 ; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to mitochondria, O 2 •- produced by NOX is dismutated into H 2 O 2 by superoxide dismutase1 (SOD1), whereas nitric oxide produced by inducible nitric oxide synthase (iNOS) reacts with O 2 •- resulting in peroxynitrite production ( 19 ). For example, ROS drive hypoxia-inducible factor 1α (HIF1α) mediated GLUT1 expression, hexokinase activity, and resultant glycolysis in response to low oxygen tension as part of the angiogenic response ( 27 ) The co-localization of neutrophil phosphofructokinase 2 with NOX2 leads to its activation, resulting in NADP+ production as its byproduct, facilitating an enhanced glycolytic rate. The increase in glycolysis rate and enhancement of NOX2 activity and the relation between these processes are still under study ( 28 ).…”
Section: Ros In Sensing and Reaction To Damagementioning
confidence: 99%